Language Attitudes of SMAN 9 Bandar Lampung Students towards French Language - Nani Kusrini; Indah Nevira Trisna; Lailatul Mukaromah (TEKNOSASTIK, 2022)
This study has two objectives, namely to describe the language attitudes of SMAN 9 Bandar Lampung students towards French language and to explain the factors influencing their language attitudes. This study used a quantitative descriptive method. Questionnaires and interviews were used for data collection.  Meanwhile, a Likert scale analysis was used to analyze the data and statistical tools were also used to determine the value of the overall language attitude component. The results of this study indicate that the language attitude of the students of class XI IPA 1 and IPA 2 of SMAN 9 Bandar Lampung is in the positive category.  The minimum threshold value of positive and negative attitudes is 50 and the average value obtained by students through the three components of language attitude in this research is 63.00 which means that the language attitude of students toward French language is positive. Then, based on factors, the factors influencing language attitudes started from the most significant are consecutively (1) language pride; (2) power and influence of language; (3) internal nature of language; (4) power and influence of language, and (5) social background of learners.